Partisipasi Masyarakat Dalam Pemeliharaan Lingkungnan Di Kelurahan Perkamil Kota Manado - Panjaitan, Erisman; Purwanto, Antonius; grace, waleleng (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study was to analyze and explain the Community's Participation in Environmental Care Village Perkamil In the city of Manado. The research methodology used is qualitative research. The results showed that the participation of the community in the form of public attendance at the discussion meeting decisions about the environment and the maintenance strategy implementation plan environmental maintenance program is already quite good, there are some people who did not attend the meeting or meetings to program planning, but few. Public participation in the implementation of environmental care is the provision of self-help in the form of power when the implementation of programs and grants (non-governmental) to support the successful implementation of the program has been quite good, the implementation of the administration and coordination of program implementation has been quite good. Community participation in maintaining and continuing maintenance of the results of program execution environment is quite active, as people realize that with them keeping all the results of the implementation of the program, it will automatically impact of the program can continue to be felt by the community. The impact is felt by the community of the results of the implementation of the enormous environmental maintenance program including the environment becomes clean and healthy and comfortable place to live. Public participation in the evaluation of program implementation issues related to preservation of the environment as a whole is good enough, because the community participated in the evaluation program, the public may submit proposals for improvements if the program found to be less successful. Keywords: CommunityÂ  Participation , Environmental